Methylguanidine and Adequacy of Dialysis - YAMAMOTO, Y.; MANJI, T.; MAEDA, K.; SAITO, A.; OHTA, K.; KOBAYASHI, K. (Jinko Zoki, 1978)
The sensitive method for the quantitative determination of all guanidino compounds in human serum was developed by the adaptation of fluorometric detection and high-pressure liquid chromatographic method. Our new analytical method for guanidino compounds was successfully applied for the evaluation of normal and uremic subjects. The cerebrospinal fluid as well as serum levels of methylguanidine, guanidine and guanidinosuccinic acid was found to be significantly elevated in uremic subjects. Methylguanidine was dialyzed more easily through a cuprophane membrane than a acetate membrane. Methylguanidine showed a similar curve of the removal rate during dialysis with creatinine and had the removal rate of 50-60%.